International Civil Aviation Organization (ICAO) - Weber, Ludwig (Kluwer Law International, 2012)
The monograph proceeds logically from the organization's genesis and historical development to the structure of its membership, its various organs and their mandates, its role in intergovernmental cooperation, and its interaction with decisions taken at the national level. Its competence, its financial management, and the nature and applicability of its data and publications are fully described.